Analysis learning language English in Elementary School During Pandemic Covid-19 - Roni Roni; Sunandar Sunandar; St Nurbaya; Sam Hermansyah; Hasan Hasan (Universitas Muhammadiyah Enrekang, 2023)
The Covid-19 pandemic has hit various parts of the world. Indonesia is one of the countries that affected plague virus Covid-19. On a number of school Which There is in Indonesia since Covid-19 implementing distance learning in the learning process. The purpose of writing this journal is to analyze the learning process carried out in elementary schools during the Covid-19 pandemic. This type of article is written using qualitative research using literature studies. Studies literature Which done in writing article This covers analysis And Also review related book, article, journal, or other relevant sources that are continuous with the title. Elementary on the exposure of this journal can it was concluded that in the conditions of the Covid-19 pandemic, it is possible for the community to do activity as where usually. Will but, on moment pandemic This of course There is form restrictions in do activity And activity the Can done in a manner online, so also with learning. At a number of school points, online learning has been implemented. On subjects Language English in level School Base can in implement with utilise media learning to support learning activities. By using learning media, then learning English will more effective effective and efficient.